A Case Report of Chronic Diarrhoea and Itchy Rash- are We Missing Something? - Farhana, Synthia; Podder, Hemonta; Ghosh, Goutam Kumar; Tarafder, Keya; Mortuza, Md Golam; Acherjya, Goutam Kumar (Bangladesh Journal of Medicine, 2023)
A proper and complete history is very important to reach the ultimate diagnosis and complete evaluation of a patient. Otherwise, the typical presentation can also be sometimes missed which leads to delay or even miss the actual diagnosis of a patient. However, we hereby present a case of a HIV (Human Immunodeficiency) patient where an incomplete history put the physician into a diagnostic dilemma and hindrance. The patient was a migrant worker and had history of sexual exposure and previous blood transfusion. Initially, he did not disclose his personal history to his general and specialist physicians. Therefore, the several consulted physicians could not reach his true diagnosis. After getting admission, we became able to explore his personal history which guided us prompt reaching in his proper diagnosis finally. Moreover, we sometimes fail to make a patient friendly environment to share everything due to social stigma, lack of welcoming environment, lack of good doctor-patient relationship. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 222-223